2019
DOI: 10.1002/ajmg.b.32765
|View full text |Cite
|
Sign up to set email alerts
|

Region‐specific insular volumetric decreases in drug‐naive, first‐episode schizophrenia and their unaffected siblings

Abstract: Decreased insular volume may be one of the anatomical alterations caused by schizophrenia. The possibility of region-specific insular volumetric reduction as an endophenotype and/or a possible treatment predictor is a critical issue with great implications for the diagnosis and prognosis of the disease. The sample of the current study comprised 44 drug-naive and first-episode patients, 42 unaffected siblings, and 44 healthy controls. A computational anatomy toolbox (CAT12) was applied to analyze the structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The insula plays a key role in monitoring internal emotional states ( 62 ) and regulating the influences of emotion on cognitive processes ( 63 , 64 ). Many studies have reported abnormalities in the insula which were related to negative symptoms in schizophrenia ( 17 , 65 ). These are in accordance with findings that a volumetric decrease of the insula relative to controls could be detected in schizophrenia with PNS ( 66 , 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…The insula plays a key role in monitoring internal emotional states ( 62 ) and regulating the influences of emotion on cognitive processes ( 63 , 64 ). Many studies have reported abnormalities in the insula which were related to negative symptoms in schizophrenia ( 17 , 65 ). These are in accordance with findings that a volumetric decrease of the insula relative to controls could be detected in schizophrenia with PNS ( 66 , 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have focused on these regional brain abnormalities when seeking to define biomarkers of SCH ( 17 , 18 ). Li et al, for example, utilized volumetric decreases in the left insula as a potential diagnostic endophenotype for SCH ( 19 ), while others have reported early decreases in global-brain functional connectivity in the bilateral anterior cingulate cortex (ACC) as a promising predictor of SCH patient therapeutic outcomes ( 20 ). In a recent article, Li et al established a novel hypothesis-driven neuroimaging biomarker of SCH through a comparison of these patients and healthy control (HC) individuals, achieving > 80% accuracy ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…The functions of insula subregions were reported in previous studies: 1) G: perception, somesthesis, and pain; 2) dIa: perception, somesthesis, and pain; action and inhibition; 3) vId/vIg: perception, somesthesis, and pain; olfaction; emotion and disgust, fear; 4) dIg: perception, somesthesis, and pain; emotion and disgust; interoception and sexuality; 5) dId: perception, somesthesis, and pain; perception and gustation; 6) vIa: perception and gustation; action and inhibition [17,18,21]. The anterior insula was the key region of the salient network which was vulnerable in FTD [19].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, subregions of vIa and dIa constitute the anterior insula. It was known that the vIa and dIa regions were associated with functions of action and inhibition [17,18,21]. Behavior disinhibition was a characteristic manifestation of bvFTD, presented as socially inappropriate behavior, loss of manners, and impulsive, rash, or careless actions [1], which was corresponding with impairment of the function in the Fig.…”
Section: Discussionmentioning
confidence: 99%